PERAN MEDIA SOSIAL DALAM PEMBENTUKAN KARAKTER SISWA SMA & SMK BHINNEKA TUNGGAL IKA, JAKARTA - Fensi, Fabianus (Universitas Bunda Mulia, 2020)
Modern human life now is living in and with social media. Social media with the power of the internet network influences the lives and actions of modern humans, including youth, and students. With the character of the network, providing fast information, archiving a lot of data, interactive, and creating content freely, social media can be seen as the most popular media, compared to conventional media, such as radio, television, magazines, and newspapers. There are many benefits obtained from social media as a learning medium to get to know the world more broadly. However, there are also many dangers posed by the use of social media. The dangers that arise can come from health, social, and even social ethical and moral problems. For this reason, the use of social media should follow generally accepted ethical standards in society. Adhering to ethical standards is the key to placing social media as public media. Social media is a tool that serves the public's need for information. The ethics of using social media is a gate keeper for filtering information. With ethics, the use of social media can be directed towards responsible and meaningful self-development in life together. Self-development can occur when social media is used from the context of needs, especially learning needs, making friends, and building positive networks with others. Social media is a reality that cannot be denied, but we can adjust it as needed.